Value of laparoscopy in the diagnosis of metastatic liver - Piñeyro, Alberto (Cirugía del Uruguay, 1986)
The author's experience in the use of fibrolaparoscopy for the diagnosis of the metastasic liver in 186 patients is said. Brief revíew of the subject and evaluatíon of the procedure is done.